Interventions for preventing back pain among office workers - a systematic review and network meta-analysis - Angelika Eisele-Metzger; Daria S Schoser; Meik D Klein; Kathrin Grummich; Guido Schwarzer; Lukas Schwingshackl; Robin Hermann; Bianca Biallas; Christiane Wilke; Joerg J Meerpohl; Cordula Braun (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVE: Back pain is common in the working population. This systematic review with network meta-analysis (NMA) aimed to compare the effects of interventions for preventing back pain among office workers. METHODS: We searched eight databases and additional sources up to March 2021. We included randomized controlled trials (RCT) and cluster RCT focusing on office workers, comparing work-related interventions aimed at preventing back pain (defined as pain in any part of the spine) to a control condition and assessing back pain and/or work absence. Further outcomes considered were adverse events and participants' satisfaction. We performed both frequentist and component NMA. Risk of bias (RoB) was evaluated using RoB 2 and certainty of the evidence (CoE) was assessed using GRADE. RESULTS: We screened 9809 records and included 24 studies with a total of 7080 participants. RoB was assessed as "some concerns" or "high" for all studies and outcomes. Included studies investigated multicomponent interventions, ergonomics, physical activity, education, behavioral interventions and no/minimal interventions. Effects were mostly not statistically significant and based on low/very low CoE. Physical activity probably reduces days of work absence slightly [mean difference (MD) -1.10, 95% confidence interval (CI) -2.07- -0.13], and combining physical activity and ergonomics may reduce back pain intensity (standardized MD -0.41, 95% CI -0.80- -0.02) when compared to no/minimal intervention. A large proportion of participants were satisfied with the interventions, adverse events were rarely assessed. CONCLUSIONS: We observed mostly minor effects of interventions on back pain and work absence among office workers. The practical relevance of these effects is questionable.